Etika Komunikasi Media Sosial pada Generasi Zilenial dalam Perspektif Pancasila - Sutrisno, Nisa Wening Asih (JCIC : Jurnal CIC Lembaga Riset dan Konsultan Sosial, 2024)
Generation Z's use of social media in communicating between lecturers and students in higher education often ignores communication ethics in accordance with Pancasila values. Unpolite interaction patterns, inappropriate choice of diction, and greetings when asking about lecture assignments are some of the problematic social media communication ethics of generation Z. This research aims to see the extent of generation Z's social media communication ethics in the perspective of Pancasila values. This is felt to be important because Pancasila is the personality of the Indonesian nation and people, so generation Z should be able to correlate their actions so that they are in accordance with Pancasila principles in communicating via social media. The research uses descriptive qualitative methods. Primary data collection uses observation, interviews and documentation. Meanwhile, secondary data comes from journals, books, magazines, articles and other library sources. Data analysis uses data triangulation through data reduction, data presentation, and drawing conclusions. The results of the research are (1) The increasing disappearance of Pancasila Ethics in generation Z communication is marked by the generation Z's lack of concern for the value of worship, weak social interaction, declining nationalism, egoism of opinion in democracy and prioritizing group solidarity even if it is wrong rather than accepting the truth. (2) Generation Z's social media behavior tends to get quick and short information through social media, so they have difficulty thinking critically about diverse information. (3) A critical attitude, deep thinking and polite language are needed in student communication with lecturers. The research conclusion is that there needs to be encouragement of example through individuals and formal institutions so that generation Z's communication ethics, especially in higher education circles involving lecturers and students, are in accordance with the principles of Pancasila.Keyword: Ethics, Communication, Social Media, Generation Z, Pancasila.